ChemInform Abstract: Homoallenyl Azines in Criss‐Cross Cycloaddition Reactions. Issue 21 (2nd May 2013) - Galeta, Juraj; Man, Stanislav; Valouskova, Aneta; Potacek, Milan
Abstract Only one diastereomer and regioisomer of type (III) or (VI) is obtained by intra‐intermolecular cycloadditions when (I) or (IV) are reacted with isocyanates or isothiocyanates as dipolarophiles.